Thiol/disulfide homeostasis in patients with ocular-active and ocular-inactive Behcet disease - Balbaba, Mehmet; Ulas, Fatih; Yildirim, Hakan; Soydan, Adem; Dal, Ali; Aydin, Stileyman (Springer, 2020)
Purpose To evaluate thiol/disulfide homeostasis in ocular-active (OA) and ocular-inactive (OI) Behcet disease (BD) patients and compare the data with healthy subjects. Methods Twenty OABD patients, 20 OIBD patients and 20 healthy control subjects were included into the study. The BD ocular attack score 24 (BOS24) scoring system was used to assess the activity of disease in ocular BD patients. Systemic activity was also evaluated using BD current activity form (BDCAF). The native thiol (NT), total thiol (TT) and disulfide levels and NT/TT, disulfide/NT and disulfide/TT ratios were measured via using an innovative and automated method. Results BOS24 and BDCAF scores were 13.25 +/- 2.32 and 4.18 +/- 2.06 in OABD patients and 0.31 +/- 0.47 and 2.14 +/- 1.98 in OIBD patients, respectively. The NT, TT levels and NT/TT ratio were significantly reduced; in contrast, the disulfide levels, disulfide/NT and disulfide/TT ratios were significantly increased in OABD and OIBD patients compared to the healthy control subjects (p < 0.05). Moreover, while the levels of NT and TT were significantly reduced, the disulfide levels as well as disulfide/NT and disulfide/TT ratios were significantly elevated between OABD and OIBD patients (p < 0.05). However, the ratio of NT/TT did not significantly differ between OABD and OIBD patients (p = 0.449). The multiple regression model including BOS24 and BDCAF score statistically significantly predicted NT level, TT level and disulfide level (p < 0.001 for all). Conclusion Thiol oxidation in BD patients resulted in a change of the thiol/disulfide balance. Therefore, thiol/disulfide homeostasis in BD patients can be used an innovative oxidative stress marker.
Keywords: Behcet disease; Thiol; Disulfide; Oxidative stress